1998
DOI: 10.1016/s0266-7681(98)80050-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Clinical Signs Improves Diagnosis of Scaphoid Fractures

Abstract: This is a prospective study evaluating the efficacy of four clinical signs believed to be useful in the diagnosis of scaphoid fracture. Two hundred and fifteen consecutive patients with suspected scaphoid fracture were examined on two separate occasions to evaluate tenderness in the anatomical snuff box (ASB), tenderness over the scaphoid tubercle (ST), pain on longitudinal compression of the thumb (LC) and the range of thumb movement (TM). At the initial examination ASB, ST and LC were all 100% sensitive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 10 publications
0
82
2
1
Order By: Relevance
“…Fifteen studies published between 1982 and 2009 assessed the diagnostic accuracy for various physical examination tests, either in isolation or in combinations, including signs such as swelling or discoloration, as well as symptoms like anatomical snuffbox tenderness, scaphoid tubercle tenderness, clamp sign, resisted pronation or supination, thumb compression-induced pain, and US pain. 5,14,[17][18][19][21][22][23]39,[41][42][43][44][45][46] None were from the United States, and 12 were from Europe. These were all prospective case series, and 11 were ED-based, while two were orthopedic clinic studies and two did not report their clinical settings.…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…Fifteen studies published between 1982 and 2009 assessed the diagnostic accuracy for various physical examination tests, either in isolation or in combinations, including signs such as swelling or discoloration, as well as symptoms like anatomical snuffbox tenderness, scaphoid tubercle tenderness, clamp sign, resisted pronation or supination, thumb compression-induced pain, and US pain. 5,14,[17][18][19][21][22][23]39,[41][42][43][44][45][46] None were from the United States, and 12 were from Europe. These were all prospective case series, and 11 were ED-based, while two were orthopedic clinic studies and two did not report their clinical settings.…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…59 There are a number of other available CDRs to aid the clinician in decision making. 22,52,53,58,[60][61][62]64,66 CDRs not only help in decision making but prevent needless imaging, reduce or eliminate radiation exposure, and keep healthcare costs down. One of the original protocols was the Brand protocol, which was developed in 1982 and specifically designed to curb excessive utilization of radiography, without compromising quality of care or increasing risk for poor outcomes.…”
Section: Evidence Of Competency Within Musculoskeletal Medicine and Ementioning
confidence: 99%
“…Pain over ASB on pronation followed by ulnar deviation of the affected wrist also gave a specificity of only 52%. 16 Parvizi et al, 10 in a prospective study involving 215 patients with suspected scaphoid fractures, showed that clinical signs of ASB tenderness, the STT and the SCT had low specificity, 19%, 30% and 48%, respectively, when used alone. However, combination of these three clinical tests within the first 24 h increased the specificity to 74%.…”
Section: Diagnostic Examinationmentioning
confidence: 99%
“…8,9 The clinician is faced with diagnostic and management dilemmas: to identify patients with scaphoid fractures, in the absence of radiographic evidence, without immobilising the majority who do not. 7,10 In 1992, the British Association for Accident and Emergency Medicine (BAEM) issued guidelines for the management of suspected scaphoid fractures. However, there still remains confusion and controversy; consequently, there is a wide variation in the management of suspected scaphoid fractures in hospitals across the UK.…”
mentioning
confidence: 99%